Răspuns :
a+b=420 b=420-a
a-a/6=2(b+a/6)
5a/6=2(420-a)+a/3
5a/6-a/3=840-2a
5a/6-a/3+2a=840
5a-2a+12a=5040
15a=5040
a=336
b=420-336=84
a-a/6=2(b+a/6)
5a/6=2(420-a)+a/3
5a/6-a/3=840-2a
5a/6-a/3+2a=840
5a-2a+12a=5040
15a=5040
a=336
b=420-336=84
a + b = 420
a - a/6= 2*(b+a/6) ⇔ 5a/6 = 2*(b+a/6) ⇒
5a = 12*(6b+a)/6 = 2*(6b+a)
deci: 5a=12b+2a adica: 3a = 12b ⇒ a = 4b
inlocuim ... 4 b+b=420 ⇒ b = 84
↓
a = 4*84 = 336
a - a/6= 2*(b+a/6) ⇔ 5a/6 = 2*(b+a/6) ⇒
5a = 12*(6b+a)/6 = 2*(6b+a)
deci: 5a=12b+2a adica: 3a = 12b ⇒ a = 4b
inlocuim ... 4 b+b=420 ⇒ b = 84
↓
a = 4*84 = 336